A descriptive review of quad‐related deaths in Australia (2011–20). (23rd December 2021) - Lower, Tony; Peachey, Kerri‐Lynn; Fragar, Lyn
Abstract: Objective : To assess Australian quad‐related deaths during the 2011–20 period in relation to introduction of the Consumer Goods (Quad Bikes) Safety Standard 2019. Methods : All Australian quad‐related deaths retrieved through the National Coronial Information System. Results : There were 155 cases, with 116 occurring on a farm and 39 in a non‐farm context. Deaths were evenly split between work (52%) and non‐work activities, however, 66% of all farm incidents involved work. Rollovers were responsible for 59% of cases and occurred largely on farms (86%), whilst working (69%). Head injury (32%) and asphyxiation (29%) were primary causes of death. Helmet use was low (<5%) in the head injury cases, with 80% of the asphyxiation cases incurring no life‐threatening injury other than being entrapped by the quad. Conclusion : Quad‐related deaths are prevalent, with minimal variation in the pattern of incidents from previous Australian studies. Rollover incidents continue to be a major problem especially in a farm context. Implications for public health : In tandem with existing efforts to enhance behavioural compliance (e.g. helmet use, no child access) and retrofitting Operator Protector Devices, these data support the introduction of the new Standard addressing vehicle stability and fitting Operator Protector Devices to limit potential for asphyxiation.